Leadership Aspects on the Nagari Government’s Competence to Use Village Funds During the Pandemic - Cici Safitri; Tengku Rika Valentina; Roni Ekha Putera (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2022)
The capacity of the Village/Nagari government is often in the spotlight on policy implementation, especially in efforts to prevent and restore the economy during the Covid-19 pandemic. Village funds are one of the priorities intended for the Village/Nagari to be used in prevention efforts to the community from the grassroots. However, these efforts have actually led to several polemics, including conflicts between the community and elements of the government that have not been optimal in carrying out policies. This study aims to explain the factors that affect the capacity of the government, especially in Nagari Pasia Laweh in the utilization of village funds during the pandemic. The research method uses descriptive qualitative data collection through in-depth interviews with several research informants from the Nagari Pasia Laweh Government. The results of this study indicate that the success of several programs and policies carried out by Nagari Pasia Laweh during the pandemic cannot be separated from the conducive leadership factor of the Wali Nagari. These factors can affect the capacity of the Nagari government as a whole, starting from efforts to prevent and utilize village funds based on a people-based approach. The commitment built by the leaders brought Nagari Pasia Laweh as the best Nagari in village fund transparency in 2020.